Development of a novel selection/counter-selection system for chromosomal gene integrations and deletions in lactic acid bacteria - Van Zyl, Winschau F. (BMC Mol Biol, 2019)
BACKGROUND: The underlying mechanisms by which probiotic lactic acid bacteria (LAB) enhance the health of the consumer have not been fully elucidated. Verification of probiotic modes of action can be achieved by using single- or multiple-gene knockout analyses of bacterial mutants in in vitro or in vivo models. We developed a novel system based on an inducible toxin counter-selection system, allowing for rapid and efficient isolation of LAB integration or deletion mutants. The Lactococcus lactis nisin A inducible promoter was used for expression of the Escherichia coli mazF toxin gene as counter-selectable marker. RESULTS: The flippase (FLP)/flippase recognition target (FRT) recombination system and an antisense RNA transcript were used to create markerless chromosomal gene integrations/deletions in LAB. Expression of NisR and NisK signalling proteins generated stable DNA integrations and deletions. Large sequences could be inserted or deleted in a series of steps, as demonstrated by insertion of the firefly bioluminescence gene and erythromycin resistance marker into the bacteriocin operons or adhesion genes of Lactobacillus plantarum 423 and Enterococcus mundtii ST4SA. CONCLUSIONS: The system was useful in the construction of L. plantarum 423 and E. mundtii ST4SA bacteriocin and adhesion gene mutants. This provides the unique opportunity to study the role of specific probiotic LAB genes in complex environments using reverse genetics analysis. Although this work focuses on two probiotic LAB strains, L. plantarum 423 and E. mundtii ST4SA, the system developed could be adapted to most, if not all, LAB species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12867-019-0127-x) contains supplementary material, which is available to authorized users.